EFFECT OF BABANDOTAN WEED (Ageratum conyzoides L.) ON ANTIOXIDANT AND PATCHOULI OIL YIELD OF Pogostemon cablin (Blanco) Benth cv. Sidikalang - Anggoro Priyatmoko; Sri Darmanti; Lilih Khotimperwati (Agric, 2023)
Weed interference results in increased synthesis of reactive oxygen species (ROS). High accumulation of ROS causes oxidative stress and stimulates the activation of the antioxidant defense system in plants. Weed interference causes biotic stress in the form of allelochemicals and abiotic stress in the form of competition for plants which results in the inhibition of growth and development in plants. Ageratum conyzoides is an annual weed in plantations and can cause biotic and abiotic stress on surrounding plants. This study aims to determine the effect of A. conyzoides interference on antioxidant content in the form of total phenol and total proline in patchouli leaves [Pogostemon cablin (Blanco) Benth cv. Sidikalang] as well as the percentage of essential oil yield from P. cablin. The study was conducted with a Complete Randomized Design (CRD) with a single factor of A. conyzoides interference levels in as many as four treatments (0, 2, 4, 6 individuals of A. conyzoides per treatment). The results concluded that higher levels of A. conyzoides interference led to an increase in total phenol and total proline in P. cablin leaves, but decreased the percentage yield of P. cablin essential oil.